Neoadjuvant and adjuvant systemic therapy for newly diagnosed stage II- IV epithelial ovary, fallopian tube, or primary peritoneal carcinoma: A systematic review. (June 2021) - Hirte, Hal; Poon, Raymond; Yao, Xiaomei; May, Taymaa; Ethier, Josee-Lyne; Petz, Lauri; Speakman, Jane; Elit, Laurie
Graphical abstract: *Defined as significant disease-related symptoms (e.g., moderate to severe pleural effusion, cachexia with poor oral intake, hypoalbuminemia and other poor nutritional status), low likelihood of achieving optimal cytoreduction (residual ≤1 cm, but ideally to no visible disease), or poor prognostic factors (e.g., poor performance status [PS] according to Eastern Cooperative Oncology Group, PS>2). **For those who are unable to tolerate paclitaxel, an alternate regimen consisting of docetaxel (75 mg/m2) may be offered with carboplatin (AUC=5). Highlights: Neoadjuvant chemotherapy can be an option for women with high-risk profiles. No data to support adding a third agent to adjuvant carboplatin and paclitaxel. A dose-dense weekly paclitaxel regime improved overall survival in Japanese women. Targeted therapy or immunotherapy offered no benefit in adjuvant setting alone. Intraperitoneal therapy can be considered for stage III optimally debulked women. Abstract: Background: To systematically review neoadjuvant and adjuvant therapy options for women with newly diagnosed stage II-IV ovarian cancer. Methods: Phase III trials were searched using MEDLINE, EMBASE, and Cochrane Library. Maintenance therapies were excluded. Results: Thirty-three trials were included. For women with high-risk profiles that would contraindicate upfront cytoreductive surgery, neoadjuvant chemotherapy can be an option. In the post-surgical adjuvant setting, the three-weekly regimen consisting of paclitaxel and carboplatin remains the standard of care. Docetaxel may be offered to those who are unable to tolerate paclitaxel. Intraperitoneal cisplatin and paclitaxel increased OS for stage III optimally debulked women (GOG 172). The intraperitoneal regimens in GOG 252 offered no survival benefit and some harms in terms of toxicity and quality of life. Conclusions: There is no evidence to support adding a third agent to the standard carboplatin and paclitaxel. Results of the iPocc study will clarify the role of intraperitoneal chemotherapy.